(untitled) (Journal of Technology and Operations Management, 2023)
Globally, all industries including franchises experience competition in business. Similar goods and services are offered by newly established brands and businesses in an attempt to attract customers and make a profit. Every business and brand should have its own approach to dealing with this issue. This paper focuses specifically on a fast-food restaurant located in Sabak Bernam, Selangor. This study will determine the factors of marketing experience based on the five dimensions of marketing experience proposed by Schmitt to enable marketing mechanisms to influence customer satisfaction. This study will use quantitative methods. A convenience sampling technique was used, and data were collected through an online survey using google forms and data from 377 respondents who came and used products/services at this fast food restaurant in Sabak Bernam, Selangor. The statistical data will be analyzed by Smart-pls version 4. The findings conclude that only related senses and experiences are positively related to customer satisfaction. Management can take action to increase their sales and profits by reading this paper and learning about how marketing affects customer satisfaction.